Polishing method and polishing composition kit
The polishing method addresses the challenge of controlling polishing selectivity by using a composition with specific components in a semiconductor substrate, enhancing the polishing speed of titanium nitride and suppressing that of silicon oxide, thus improving the selectivity ratio.
Patent Information
- Application Number
- JP2023169681
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-29
- Publication Date
- 2025-04-10
AI Technical Summary
There is a demand for controlling the polishing selectivity of materials containing multiple film species, where the polishing speed of one film species is enhanced while the polishing speed of another is suppressed.
A polishing method using a composition that includes abrasive grains with a positive zeta potential, an organic acid, a nonionic surfactant as a polishing inhibitor, and an oxidizing agent, where the components are prepared in separate liquids and mixed just before or during polishing.
This method effectively controls the polishing selectivity, enhancing the polishing speed of certain film species, such as titanium nitride, while suppressing the polishing speed of others, such as silicon oxide, thereby improving the polishing selectivity ratio.
Smart Images

Figure 2025059537000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a polishing method and a polishing composition kit. [Background technology]
[0002] In recent years, with the trend toward multi-layer wiring on the surface of semiconductor substrates, a so-called chemical mechanical polishing (CMP) technique is used to polish and flatten semiconductor substrates when manufacturing devices. CMP is a method for flattening the surface of an object to be polished (object to be polished) such as a semiconductor substrate by using a polishing composition (slurry) containing abrasive grains such as silica, alumina, ceria, etc., an anticorrosive agent, a surfactant, etc., and the object to be polished (object to be polished) is a film containing silicon, polysilicon, silicon oxide (silicon oxide), silicon nitride, titanium nitride, titanium, tantalum nitride, tantalum, etc., wiring, plugs, etc. made of metals such as copper and tungsten, etc.
[0003] In particular, focusing on the polishing of titanium nitride, Patent Document 1 discloses that titanium films and titanium nitride films can be polished using a polishing composition containing an abrasive, at least one complexing agent selected from the group consisting of hydrogen peroxide, citric acid, lactic acid, tartaric acid, succinic acid, acetic acid, oxalic acid, and salts thereof, and a film-forming agent such as benzotriazole (BTA). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 11-021546 Summary of the Invention [Problem to be solved by the invention]
[0005] Recently, there has been a demand for controlling the polishing selectivity, that is, for an object to be polished that contains two or more different film types, by increasing the polishing rate of one film type and suppressing the polishing rate of another film type.
[0006] Therefore, an object of the present invention is to provide a means for controlling the polishing selectivity, that is, increasing the polishing rate of one film type and suppressing the polishing rate of another film type, in a polishing object containing two or more different film types. [Means for solving the problem]
[0007] In order to solve the above problems, the present inventor has conducted extensive research. As a result, the inventor has found that the above problems can be solved by a polishing method for polishing an object to be polished using a polishing composition, the polishing composition comprising an abrasive grain, an acid, a polishing inhibitor, an oxidizing agent, and a dispersion medium, the abrasive grain has a positive zeta potential, the acid is an organic acid, the polishing inhibitor comprises a nonionic surfactant, the components of the polishing composition are prepared separately as a first liquid and a second liquid, the first liquid comprises the abrasive grain and the dispersion medium, the second liquid comprises the acid, the polishing inhibitor, the oxidizing agent, and the dispersion medium, and the first liquid and the second liquid are mixed immediately before or during polishing the object to be polished, and has completed the present invention. Effect of the Invention
[0008] According to the present invention, there is provided a means for controlling the polishing selectivity, that is, increasing the polishing rate of one film type and suppressing the polishing rate of another film type, in a polishing object containing two or more different film types. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The following describes the embodiments of the present invention, but the present invention is not limited to the following embodiments and can be modified in various ways within the scope of the claims. The embodiments described in this specification can be combined in any way to form other embodiments. In this specification, unless otherwise specified, operations and measurements of physical properties are performed under the conditions of room temperature (20°C to 25°C) and relative humidity of 40% RH to 50% RH.
[0010] The present invention is a polishing method for polishing an object (substrate) using a polishing composition, the polishing composition comprising an abrasive, an acid, a polishing inhibitor, an oxidizing agent, and a dispersion medium, the abrasive has a positive zeta potential, the acid is an organic acid, the polishing inhibitor comprises a nonionic surfactant, the components of the polishing composition are prepared separately as a first liquid and a second liquid, the first liquid comprises the abrasive and the dispersion medium, the second liquid comprises the acid, the polishing inhibitor, the oxidizing agent, and the dispersion medium, and the first liquid and the second liquid are mixed immediately before or during polishing of the object. According to such a polishing method, in an object to be polished that includes two or more different film types, the polishing rate of a certain film type can be improved and the polishing rate of a certain film type can be suppressed. That is, according to the polishing method of the present invention, the polishing selectivity can be controlled in an object to be polished that includes two or more different film types. The present inventor presumes the mechanism by which such an effect is obtained by the present invention as follows. However, the following mechanism is an assumed mechanism taking as an example the case where an object to be polished contains a titanium nitride film and a silicon oxide film, and the scope of the present invention is not limited thereto.
[0011] In one embodiment of the present invention, the objective is to improve the polishing rate of the titanium nitride film and suppress the polishing rate of the silicon oxide film. An oxidizing agent is used to improve the polishing rate of the titanium nitride film. Abrasive grains having a positive zeta potential are used to suppress the polishing rate by utilizing electrostatic repulsion with the silicon oxide film. However, the polishing selectivity ratio expressed by the polishing rate of the titanium nitride film / the polishing rate of the silicon oxide film (hereinafter, also simply referred to as the "polishing selectivity ratio of titanium nitride / silicon oxide") is not sufficient. Therefore, a compound that does not affect the titanium nitride film and suppresses the polishing rate of the silicon oxide film was earnestly studied. As a result, a compound that selectively adsorbs to the silicon oxide film and inhibits contact with the abrasive grains by containing an oxidizing agent and combining it with an organic acid was found. That is, the present inventors have found that a nonionic surfactant can be a polishing suppressor for the silicon oxide film under certain conditions. The reason why nonionic surfactant does not affect titanium nitride film and selectively adsorbs to silicon oxide film is unclear, but it is considered that the polarity of nonionic surfactant and the polarity of silicon oxide repeating unit are similar, and have high affinity.In the polishing composition of the present invention, under specific conditions, nonionic surfactant selectively adsorbs on the surface of silicon oxide film, and forms a film that protects the surface of silicon oxide film.This suppresses the contact between silicon oxide film and abrasive grains, suppresses the polishing speed of silicon oxide film, and is considered to be able to increase the polishing selectivity of titanium nitride / silicon oxide.
[0012] However, the inventors of the present invention found that the polishing composition of the present invention is prone to generate agglomerates when stored for a long time, and that there is room for improvement in terms of stability over time. The agglomerates are considered to be mainly abrasive grain aggregates in which a plurality of abrasive grains are aggregated to have a larger particle size. The frictional force of such abrasive grain aggregates on the polishing surface during polishing varies depending on the size. Therefore, when a polishing composition containing agglomerates is used for polishing, the polishing rate of the silicon oxide film increases, and the polishing selectivity of titanium nitride / silicon oxide decreases. In response to such a problem, the inventors of the present invention have investigated a method for suppressing the generation of agglomerates even after long-term storage and obtaining a desired polishing selectivity of titanium nitride / silicon oxide, and have completed the present invention.
[0013] As described above, the inventor has discovered that the problem of providing a polishing composition having a high titanium nitride / silicon oxide polishing selectivity ratio can be solved by a polishing method in which the components of the polishing composition are prepared separately as a first liquid containing abrasive grains and a dispersing medium, and a second liquid containing an acid, a polishing inhibitor, an oxidizing agent and a dispersing medium, and the first liquid and the second liquid are mixed immediately before or during polishing of an object to be polished.
[0014] Therefore, in one embodiment of the present invention, the above polishing method can polish a titanium nitride film at a higher polishing rate than a silicon oxide film (i.e., the polishing selectivity, expressed as the polishing rate of the titanium nitride film / the polishing rate of the silicon oxide film, is high). Therefore, according to one embodiment of the present invention, the polishing selectivity of titanium nitride / silicon oxide can be improved.
[0015] The polishing method of the present invention will now be described in detail.
[0016] <Polishing method> The polishing method according to the present invention is a method for polishing an object to be polished. Specifically, in the polishing method according to the present invention, the components of a specific polishing composition are prepared separately as a first liquid and a second liquid, and the first liquid and the second liquid are mixed immediately before or during polishing of an object to be polished. Here, the specific polishing composition contains abrasive grains, an acid, a polishing inhibitor, an oxidizing agent, and a dispersion medium, the abrasive grains have a positive zeta potential, the acid is an organic acid, and the polishing inhibitor contains a nonionic surfactant. Such a specific polishing composition is prepared separately as a first liquid containing abrasive grains and a dispersion medium, and a second liquid containing an acid, a polishing inhibitor, an oxidizing agent, and a dispersion medium.
[0017] The polishing method according to the present invention can control the polishing selectivity, that is, improve the polishing rate of one film type and suppress the polishing rate of another film type, in a polishing object containing two or more different film types. The polishing method according to one embodiment of the present invention can polish an object containing silicon oxide and titanium nitride at a specific polishing rate ratio. The polishing method according to the present invention can be preferably applied to polishing (e.g., finish polishing) an object containing silicon oxide and titanium nitride.
[0018] In the polishing method according to the present invention, the first liquid contains abrasive grains and a dispersion medium, and the second liquid contains an acid, a polishing inhibitor, an oxidizing agent, and a dispersion medium. Here, the first liquid and the second liquid may be used for polishing as they are, or the first liquid and / or the second liquid may be diluted with the dispersion medium during or immediately before polishing, or when the first liquid and the second liquid are mixed during or immediately before polishing, a dispersion medium may be mixed at the same time as the third liquid.
[0019] First, the components of the first and second liquids used in the polishing method according to the present invention will be described.
[0020] [First liquid] [Abrasive grain] The first liquid according to the present invention contains abrasive grains. The abrasive grains contained in the first liquid according to the present invention have a positive zeta potential. The abrasive grains are preferably cation-modified silica (silica having a cationic group), and more preferably cation-modified colloidal silica (colloidal silica having a cationic group). The abrasive grains may be used alone or in combination of two or more kinds. In addition, the abrasive grains may be commercially available products or synthetic products.
[0021] The method for producing colloidal silica includes a sodium silicate method and a sol-gel method, and colloidal silica produced by either method can be suitably used as the abrasive grain according to the present invention. However, from the viewpoint of reducing metal impurities, colloidal silica produced by the sol-gel method is preferred. Colloidal silica produced by the sol-gel method is preferred because it contains less metal impurities that are diffusible in semiconductors and less corrosive ions such as chloride ions. Colloidal silica can be produced by the sol-gel method using a conventionally known method, and specifically, colloidal silica can be obtained by hydrolysis and condensation reaction using a hydrolyzable silicon compound (e.g., alkoxysilane or its derivative) as a raw material.
[0022] Here, cation-modified means a state in which a cationic group (e.g., an amino group or a quaternary ammonium group) is bonded to the surface of silica (preferably colloidal silica). According to a preferred embodiment of the present invention, the cation-modified silica particles are amino-modified silica particles, more preferably amino-modified colloidal silica particles. According to such an embodiment, the above-mentioned effects can be further improved.
[0023] To cationically modify silica (colloidal silica), a silane coupling agent having a cationic group (e.g., an amino group or a quaternary ammonium group) is added to silica (colloidal silica) and reacted at a predetermined temperature for a predetermined time. In a preferred embodiment of the present invention, the cationically modified silica is obtained by fixing a silane coupling agent having an amino group or a silane coupling agent having a quaternary ammonium group to the surface of silica (more preferably colloidal silica).
[0024] In this case, the silane coupling agent used may be, for example, that described in JP-A-2005-162533.Specific examples of the silane coupling agent include N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltriethoxysilane, γ-aminopropyltriethoxysilane ((3-aminopropyl)triethoxysilane), γ-aminopropyltrimethoxysilane, γ-triethoxysilyl-N-(α,γ-dimethyl-butylidene)propylamine, N-phenyl-γ-aminopropyltrimethoxysilane, N-(vinylbenzyl)-β-aminoethyl-γ-aminopropyltriethoxysilane hydrochloride, octadecyldimethyl-(γ-trimethoxysilylpropyl)-ammonium chloride, and N-trimethoxysilylpropyl-N,N,N-trimethylammonium chloride. Among them, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltriethoxysilane, γ-aminopropyltriethoxysilane, and γ-aminopropyltrimethoxysilane are preferably used because of their good reactivity with colloidal silica. In the present invention, the silane coupling agent may be used alone or in combination of two or more kinds.
[0025] The silane coupling agent can be added to silica (colloidal silica) as it is or after diluting with a hydrophilic organic solvent or pure water. By diluting with a hydrophilic organic solvent or pure water, the formation of aggregates can be suppressed. When diluting the silane coupling agent with a hydrophilic organic solvent or pure water, the silane coupling agent may be diluted with the hydrophilic organic solvent or pure water so that the concentration of the silane coupling agent is preferably 0.01 g or more and 1 g or less, more preferably 0.1 g or more and 0.7 g or less in 1 L of the hydrophilic organic solvent or pure water. The hydrophilic organic solvent is not particularly limited, but examples thereof include lower alcohols such as methanol, ethanol, isopropanol, and butanol.
[0026] In addition, the amount of cationic groups introduced to the surface of silica (colloidal silica) can be adjusted by adjusting the amount of silane coupling agent added. The amount of silane coupling agent used is not particularly limited, but is preferably 0.1 mM (mmol / L) or more and 5 mM or less, more preferably 0.5 mM or more and 3 mM or less, relative to the reaction solution.
[0027] The treatment temperature when the silica (colloidal silica) is cationically modified with the silane coupling agent is not particularly limited, and may be from room temperature (e.g., 25°C) to a temperature about the boiling point of the dispersion medium in which the silica (colloidal silica) is dispersed, specifically, from 0°C to 100°C, and preferably from room temperature (e.g., 25°C) to 90°C.
[0028] Here, the zeta potential of the abrasive grains in the first liquid is not particularly limited as long as the zeta potential of the abrasive grains in the polishing composition is within the range described below, but for example, the lower limit of the zeta potential of the abrasive grains in the first liquid is preferably 5 mV or more, more preferably 10 mV or more, even more preferably 15 mV or more, particularly preferably 18 mV or more, and most preferably 20 mV or more. Also, the upper limit of the zeta potential of the abrasive grains in the first liquid is preferably 70 mV or less, more preferably 60 mV or less, even more preferably 50 mV or less, particularly preferably 40 mV or less, and most preferably 35 mV or less. That is, the zeta potential of the abrasive grains in the first liquid is preferably 5 mV or more and 70 mV or less, more preferably 10 mV or more and 60 mV or less, even more preferably 15 mV or more and 50 mV or less, particularly preferably 18 mV or more and 40 mV or less, and most preferably 20 mV or more and 35 mV or less.
[0029] The shape of the abrasive grains is not particularly limited, and may be spherical or non-spherical. Specific examples of non-spherical shapes include polygonal prisms such as triangular prisms and square prisms, cylinders, bales in which the center of a cylinder is bulged out more than the ends, donut shapes in which the center of a disk is penetrated, plates, so-called cocoons with a constriction in the center, so-called association-type spheres in which multiple particles are integrated, so-called confetti shapes with multiple protrusions on the surface, and rugby ball shapes, and various other shapes are not particularly limited.
[0030] The average primary particle diameter of the abrasive grains is preferably 1 nm or more, more preferably 3 nm or more, and even more preferably 5 nm or more. When the average primary particle diameter of the abrasive grains is within the above lower limit, the polishing speed of a certain film type can be improved and the polishing speed of another film type can be suppressed in a polishing object containing two or more different film types. According to one embodiment, as the average primary particle diameter of the abrasive grains increases, the polishing speed of the titanium nitride film increases. In addition, the average primary particle diameter of the abrasive grains is preferably 100 nm or less, more preferably 50 nm or less, and even more preferably 30 nm or less. When the average primary particle diameter of the abrasive grains is within the above upper limit, the polishing speed of a certain film type can be improved and the polishing speed of another film type can be suppressed in a polishing object containing two or more different film types. According to one embodiment, as the average primary particle diameter of the abrasive grains decreases, the polishing speed of the titanium nitride film becomes higher than the polishing speed of the silicon oxide film (the polishing selectivity becomes higher).
[0031] That is, the average primary particle size of the abrasive grains is preferably 1 nm or more and 100 nm or less, more preferably 3 nm or more and 50 nm or less, and even more preferably 5 nm or more and 30 nm or less. The average primary particle size of the abrasive grains can be calculated, for example, based on the specific surface area (SA) of the abrasive grains calculated by the BET method and the density of the abrasive grains. More specifically, the average primary particle size of the abrasive grains is a value measured by the method described in the Examples.
[0032] The average secondary particle diameter of the abrasive grains is preferably 15 nm or more, more preferably 20 nm or more, and even more preferably 25 nm or more. When the average secondary particle diameter of the abrasive grains is within the above lower limit, the polishing speed of a certain film type can be improved and the polishing speed of another film type can be suppressed in a polishing object containing two or more different film types. According to one embodiment, as the average secondary particle diameter of the abrasive grains increases, the resistance during polishing decreases, and stable polishing of the titanium nitride film is possible. In addition, the average secondary particle diameter of the abrasive grains is preferably 200 nm or less, more preferably 150 nm or less, and even more preferably 100 nm or less. When the average secondary particle diameter of the abrasive grains is within the above upper limit, the polishing speed of a certain film type can be improved and the polishing speed of another film type can be suppressed in a polishing object containing two or more different film types. According to one embodiment, as the average secondary particle diameter of the abrasive grains decreases, the surface area per unit mass of the abrasive grains increases, the frequency of contact with the polishing object increases, and the polishing speed of the titanium nitride film is further improved. That is, the average secondary particle size of the abrasive grains is preferably 15 nm or more and 200 nm or less, more preferably 20 nm or more and 150 nm or less, and even more preferably 25 nm or more and 100 nm or less. The average secondary particle size of the abrasive grains can be measured, for example, by a dynamic light scattering method represented by a laser diffraction scattering method, and specifically, the value measured by the method described in the Examples is used.
[0033] The ratio of the average secondary particle diameter to the average primary particle diameter of the abrasive grains (average secondary particle diameter / average primary particle diameter, hereinafter also referred to as "average degree of association") is preferably more than 1.0, more preferably 1.1 or more, and even more preferably 1.2 or more. When the average degree of association of the abrasive grains is at the lower limit, the polishing speed of a certain film type can be improved and the polishing speed of another film type can be suppressed in a polishing object containing two or more different film types. According to one embodiment, as the average degree of association of the abrasive grains increases, the polishing speed of the titanium nitride film can be further improved. In addition, the average degree of association of the abrasive grains is preferably 4 or less, more preferably 3.5 or less, and even more preferably 3 or less. When the average degree of association of the abrasive grains is at the upper limit, the polishing speed of a certain film type can be improved and the polishing speed of another film type can be suppressed in a polishing object containing two or more different film types. According to one embodiment, as the average degree of association of the abrasive grains decreases, the polishing speed of the titanium nitride film becomes higher than the polishing speed of the silicon oxide film (the polishing selectivity becomes higher). That is, the average degree of association of the abrasive grains is preferably more than 1.0 and not more than 4, more preferably 1.1 or more and 3.5 or less, and even more preferably 1.2 or more and 3 or less.
[0034] The average degree of association of the abrasive grains is obtained by dividing the average secondary particle size of the abrasive grains by the average primary particle size of the abrasive grains.
[0035] The upper limit of the aspect ratio of the abrasive grain is not particularly limited, but is preferably less than 2.0, more preferably 1.8 or less, and even more preferably 1.5 or less. In such a range, defects on the surface of the object to be polished can be further reduced. The aspect ratio is the average value obtained by taking the smallest rectangle that circumscribes the image of the abrasive grain by a scanning electron microscope, and dividing the length of the long side of the rectangle by the length of the short side of the same rectangle, and can be obtained using general image analysis software. The lower limit of the aspect ratio of the abrasive grain is not particularly limited, but is preferably 1.0 or more.
[0036] The size of the abrasive grains (average primary particle size, average secondary particle size, aspect ratio, etc.) can be appropriately controlled by selecting the manufacturing method of the abrasive grains, etc.
[0037] In the first liquid according to the present invention, the abrasive grains may be used alone or in combination of two or more kinds. In addition, the abrasive grains to be used may be either commercially available products or synthetic products.
[0038] The content (concentration) of the abrasive grains in the first liquid is not particularly limited as long as the content of the abrasive grains in the polishing composition is within the range described below, but is preferably 0.1 mass% or more, more preferably 0.2 mass% or more, even more preferably 0.5 mass% or more, and particularly preferably more than 0.5 mass% based on the total mass of the first liquid. The upper limit of the content of the abrasive grains in the first liquid is preferably 10 mass% or less, more preferably 5 mass% or less, even more preferably 4 mass% or less, and particularly preferably less than 4 mass% based on the total mass of the first liquid. That is, the content of the abrasive grains in the first liquid is preferably 0.1 mass% or more and 10 mass% or less, more preferably 0.2 mass% or more and 5 mass% or less, even more preferably 0.5 mass% or more and 4 mass% or less, and particularly preferably more than 0.5 mass% and less than 4 mass% based on the total mass of the first liquid. In one embodiment, the content (concentration) of the abrasive grains in the first liquid is 0.5 mass% or more and 5.0 mass% or less.
[0039] If the content of the abrasive grains is within this range, the stability of the first liquid will be even better. When the first liquid contains two or more types of abrasive grains, the content of the abrasive grains refers to the total amount of these.
[0040] When cation-modified silica is used as the abrasive in the first liquid according to the present invention, other abrasives than cation-modified silica may be further included within the range that does not impair the effect of the present invention. Such other abrasives may be any of inorganic particles, organic particles, and organic-inorganic composite particles. Specific examples of inorganic particles include unmodified silica, particles made of metal oxides such as alumina, ceria, and titania, silicon nitride particles, silicon carbide particles, and boron nitride particles. Specific examples of organic particles include polymethylmethacrylate (PMMA) particles.
[0041] [Second liquid] [Polishing inhibitor] The second liquid according to the present invention contains a nonionic surfactant as a polishing suppressor. The nonionic surfactant has a function of suppressing the polishing rate of a certain film type (e.g., a silicon oxide film). In one embodiment, the nonionic surfactant has a function of suppressing the polishing rate of a silicon oxide film. Thus, according to one embodiment, the polishing suppressor is a silicon oxide polishing suppressor. The nonionic surfactant may be used alone or in combination of two or more kinds. Furthermore, the nonionic surfactant may be a commercially available product or a synthetic product.
[0042] Examples of the nonionic surfactant used in the second liquid according to the present invention include alkyl betaines, alkyl amine oxides, polyoxyalkylene glycols, polyoxyalkylene alkyl ethers, sorbitan fatty acid esters, glycerin fatty acid esters, polyoxyalkylene fatty acid esters, polyoxyalkylene alkylamines, and alkyl alkanolamides. Among them, polyoxyalkylene glycols and polyoxyalkylene alkyl ethers are preferred from the viewpoint of controlling the polishing selectivity in an object to be polished that includes two or more different film types (for example, from the viewpoint of improving the polishing selectivity of titanium nitride / silicon oxide).
[0043] In a preferred embodiment, the second liquid according to the present invention contains a compound having a polyoxyalkylene glycol structure (hereinafter referred to as a "polyoxyalkylene glycol compound") as a nonionic surfactant. In a more preferred embodiment, the second liquid according to the present invention contains a compound having one or more structures selected from the group consisting of a polyethylene glycol structure and a polypropylene glycol structure as a nonionic surfactant. By using a polyoxyalkylene glycol compound as a nonionic surfactant, the effect of suppressing the polishing rate of the silicon oxide film is further exerted. The polyoxyalkylene glycol compound may be used alone or in combination of two or more kinds. In addition, the polyoxyalkylene glycol compound may be a commercially available product or a synthetic product.
[0044] The type of polyoxyalkylene glycol compound is not particularly limited, and examples thereof include polyethylene glycol, polypropylene glycol, polyethylene glycol-polypropylene glycol random copolymer, polyethylene glycol-polytetramethylene glycol random copolymer, polypropylene glycol-polytetramethylene glycol random copolymer, polyethylene glycol-polypropylene glycol-polytetramethylene glycol random copolymer, polyethylene glycol-polypropylene glycol block copolymer, polypropylene glycol-polyethylene glycol-polypropylene glycol triblock copolymer, polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer, etc. Among these, polypropylene glycol is preferred.
[0045] The number average molecular weight (Mn) of the nonionic surfactant (preferably a polyoxyalkylene glycol compound) is preferably 100 or more, more preferably 150 or more, even more preferably 200 or more, particularly preferably 250 or more, and most preferably 300 or more. The weight average molecular weight (Mw) of the nonionic surfactant (preferably a polyoxyalkylene glycol compound) may be, for example, 2000 or less, preferably less than 1000, more preferably 900 or less, even more preferably 800 or less, particularly preferably 700 or less, and most preferably 600 or less. That is, the number average molecular weight (Mn) of the nonionic surfactant (preferably a polyoxyalkylene glycol compound) is preferably 100 or more and less than 1000, more preferably 150 or more and 900 or less, even more preferably 200 or more and 800 or less, particularly preferably 250 or more and 700 or less, and most preferably 300 or more and 600 or less. In one embodiment, the number average molecular weight (Mn) of the nonionic surfactant (preferably a polyoxyalkylene glycol-based compound) is 200 or more and less than 1000. In one embodiment, the polishing inhibitor is a polyethylene glycol or polypropylene glycol having a number average molecular weight of 200 or more and less than 1000.
[0046] In this specification, the number average molecular weight (Mn) of the nonionic surfactant can be measured by gel permeation chromatography (GPC) using polyethylene glycol as a standard substance. For example, it can be measured under the following conditions.
[0047] [Measurement of number average molecular weight (Mn) of nonionic surfactants] The number average molecular weight (Mn) of the nonionic surfactant was determined by gel permeation chromatography (GPC) using the number average molecular weight (converted into polyethylene glycol). The number average molecular weight was measured using the following apparatus and conditions: GPC equipment: Shimadzu Corporation Model: Prominence + ELSD detector (ELSD-LTII) Column: VP-ODS (Shimadzu Corporation) Mobile phase A: Methanol B: 1% acetic acid solution Flow rate: 1mL / min Detector: ELSD temp. 40℃, Gain 8, N2GAS 350kPa Oven temperature: 40℃ Injection volume: 40μL.
[0048] The content (concentration) of the nonionic surfactant in the second liquid is not particularly limited as long as the content of the abrasive grains in the polishing composition is within the range described below, but is preferably 0.001 mass% or more, more preferably 0.002 mass% or more, even more preferably 0.005 mass% or more, particularly preferably 0.008 mass% or more, and most preferably 0.01 mass% or more, based on the total mass of the second liquid. The content of the nonionic surfactant in the second liquid is preferably 10 mass% or less, more preferably 5 mass% or less, even more preferably 2 mass% or less, particularly preferably 1 mass% or less, and most preferably 0.8 mass% or less, based on the total mass of the second liquid. If the content of the nonionic surfactant is within such a range, the stability of the second liquid will be even better.
[0049] That is, the content (concentration) of the nonionic surfactant in the second liquid is preferably 0.001 mass% or more and 10 mass% or less, more preferably 0.002 mass% or more and 5 mass% or less, even more preferably 0.005 mass% or more and 2 mass% or less, particularly preferably 0.008 mass% or more and 1 mass% or less, and most preferably 0.01 mass% or more and 0.8 mass% or less, relative to the total mass of the second liquid.
[0050] [acid] The second liquid according to the present invention contains an organic acid as an acid. The organic acid acts as a pH adjuster. The organic acid includes carboxylic acids and sulfur-containing organic acids.
[0051] Specific examples of carboxylic acids include formic acid, acetic acid, propionic acid, butyric acid, valeric acid, 2-methylbutyric acid, n-hexanoic acid, 3,3-dimethylbutyric acid, 2-ethylbutyric acid, 4-methylpentanoic acid, n-heptanoic acid, 2-methylhexanoic acid, n-octanoic acid, 2-ethylhexanoic acid, benzoic acid, glycolic acid, salicylic acid, glyceric acid, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, maleic acid, phthalic acid, malic acid, tartaric acid, citric acid, and lactic acid. Specific examples of sulfur-containing organic acids include methanesulfonic acid, ethanesulfonic acid, 10-camphorsulfonic acid, and isethionic acid. These acids may be used alone or in combination of two or more.
[0052] The organic acid is preferably a sulfur-containing organic acid, more preferably an organic acid having a sulfonic acid group.Thus, the organic acid is preferably methanesulfonic acid, ethanesulfonic acid, 10-camphorsulfonic acid, isethionic acid, more preferably 10-camphorsulfonic acid, and particularly preferably 10-camphorsulfonic acid.
[0053] The content (concentration) of the organic acid in the second liquid is not particularly limited as long as the content of the abrasive grains in the polishing composition is within the range described below, but is preferably 0.001 mass% or more, more preferably 0.005 mass% or more, based on the total mass of the second liquid. The content of the organic acid in the second liquid is preferably 10 mass% or less, more preferably 5 mass% or less, based on the total mass of the second liquid. If the content of the acid is within this range, the stability of the second liquid will be even better.
[0054] In the second liquid according to the present invention, the organic acid plays a role as a pH adjuster for the polishing composition, and the amount of the organic acid added may be appropriately adjusted so that the pH of the polishing composition is, for example, 2 to 4. For example, when 10-camphorsulfonic acid is used, the amount of the organic acid added is preferably 0.005% by mass to 1% by mass, more preferably 0.008% by mass to 0.500% by mass, and particularly preferably 0.010% by mass to 0.100% by mass, based on the total mass of the polishing composition. In one embodiment, the content of 10-camphorsulfonic acid is 0.01% by mass to 0.03% by mass, based on the total mass of the polishing composition.
[0055] [Oxidizing agent] The second liquid according to the present invention contains an oxidizing agent. The oxidizing agent causes an oxidation reaction with the surface of the object to be polished during the polishing process, which can reduce the hardness of the surface and make the surface brittle. By using the oxidizing agent, the polishing selectivity can be controlled in the object to be polished that includes two or more different film types. According to one embodiment, the oxidizing agent can effectively improve the polishing speed of the object to be polished, such as a titanium nitride film.
[0056] The oxidizing agent is not particularly limited as long as it has a sufficient redox potential to oxidize the surface of the object to be polished. For example, the oxidizing agent may be a substance having a redox potential higher than the redox potential of the object (material) to be polished at the pH at which polishing is performed. Here, the pH at which the polishing is performed is usually the same as the pH of the polishing composition. The redox potential of the object (material) to be polished is determined by dispersing the powder of the material in water to make a slurry, adjusting the pH of the slurry to the same as that of the polishing composition, and then measuring the redox potential of the slurry (the redox potential against the standard hydrogen electrode at a liquid temperature of 25°C) using a commercially available redox potentiometer.
[0057] Examples of oxidizing agents include peroxides such as hydrogen peroxide, sodium peroxide, barium peroxide, and ozone water; nitric acids such as iron nitrate, silver nitrate, and aluminum nitrate; persulfuric acids such as peroxomonosulfuric acid and peroxodisulfuric acid; chloric acids such as chloric acid, perchloric acid, chlorous acid, and hypochlorous acid; bromic acids such as bromic acid and hypobromous acid; iodic acids such as iodic acid and hypoiodous acid; periodic acids; ferric acids such as potassium ferrate; permanganic acids such as sodium permanganate and potassium permanganate; chromates such as potassium chromate and potassium dichromate; dichromates; vanadium. Vanadates such as ammonium vanadate, sodium vanadate, and potassium vanadate; ruthenic acids such as perruthenic acid or its salts; molybdic acids such as molybdic acid and its salts such as ammonium molybdate and disodium molybdate; rhenic acids such as perrhenic acid or its salts; tungstic acids such as tungstic acid and its salts such as disodium tungstate; iron (III) salts; silver (II) salts; peroxolinic acid, peroxoboric acid, performic acid, peracetic acid, perbenzoic acid, perphthalic acid, dichloroisocyanuric acid, and their salts. Among these, peroxides such as hydrogen peroxide, sodium peroxide, barium peroxide, and ozone water are preferred, and hydrogen peroxide is more preferred.
[0058] The oxidizing agent may be used alone or in appropriate combination of two or more kinds.
[0059] In the second liquid according to the present invention, the oxidizing agent is preferably hydrogen peroxide. By using hydrogen peroxide, it is possible to control the polishing selectivity of an object to be polished that includes two or more different types of films. According to one embodiment, the oxidizing agent can polish a titanium nitride film at a higher polishing rate than a silicon oxide film.
[0060] The second liquid according to the present invention may contain an oxidizing agent other than hydrogen peroxide. However, in order to more effectively exert the effects of the present invention, it is preferable that the second liquid does not contain an oxidizing agent other than hydrogen peroxide.
[0061] The content of the oxidizing agent in the second liquid is not particularly limited as long as the content of the oxidizing agent in the polishing composition is within the range described below, but it is appropriate to make it 0.001 mol / L (1 mM) or more. From the viewpoint of the stability of the second liquid, in some embodiments, the content of the oxidizing agent is preferably 0.005 mol / L (5 mM) or more, more preferably 0.01 mol / L (10 mM) or more, even more preferably 0.03 mol / L (30 mM) or more, particularly preferably 0.05 mol / L (50 mM) or more, and most preferably 0.08 mol / L (80 mM) or more. Furthermore, from the viewpoint of the stability of the second liquid, the content of the oxidizing agent is suitably 10 mol / L (10,000 mM) or less, preferably 5 mol / L (5,000 mM) or less, more preferably 3 mol / L (3,000 mM) or less (for example, 2.5 mol / L (2,500 mM) or less, or 2 mol / L (2,000 mM) or less), even more preferably 1 mol / L (1,000 mM) or less, particularly preferably 0.5 mol / L (500 mM) or less, and most preferably 0.3 mol / L (300 mM) or less.
[0062] In view of the above, the content of the oxidizing agent in the second liquid is suitably 0.001 mol / L or more and 10 mol / L or less, preferably 0.005 mol / L or more and 5 mol / L or less, more preferably 0.01 mol / L or more and 3 mol / L or less, even more preferably 0.03 mol / L or more and 1 mol / L or less, particularly preferably 0.05 mol / L or more and 0.5 mol / L or less, and most preferably 0.08 mol / L or more and 0.3 mol / L or less.
[0063] [Dispersion medium] The first and second liquids according to the present invention contain a dispersion medium for dispersing each component. Examples of the dispersion medium used in the first and second liquids include water; alcohols such as methanol, ethanol, and ethylene glycol; ketones such as acetone, and mixtures thereof. Of these, water is preferred as the dispersion medium. That is, according to a preferred embodiment of the present invention, the dispersion medium contains water. According to a more preferred embodiment of the present invention, the dispersion medium is substantially composed of water. Note that the above term "substantially" means that a dispersion medium other than water may be included as long as the effects of the present invention can be achieved. More specifically, the dispersion medium is preferably composed of 90% by mass or more and 100% by mass or less of water and 0% by mass or more and 10% by mass or less of a dispersion medium other than water, and more preferably 99% by mass or more and 100% by mass or less of water and 0% by mass or more and 1% by mass or less of a dispersion medium other than water. Most preferably, the dispersion medium is water.
[0064] From the viewpoint of not inhibiting the action of the components contained in the first liquid and the second liquid, the dispersion medium is preferably water containing as few impurities as possible. Specifically, pure water or ultrapure water from which impurity ions are removed by an ion exchange resin and then foreign matter is removed by passing through a filter, or distilled water is more preferable.
[0065] [Other ingredients] The first and second liquids according to the present invention may further contain known additives that can be used in polishing compositions, such as complexing agents, preservatives, antifungal agents, water-soluble polymers, dissolution aids, surfactants other than nonionic surfactants, and pH adjusters, within the range that does not inhibit the effects of the present invention. The first and second liquids according to the present invention are acidic. For this reason, it is more preferable that the first and / or second liquids contain an antifungal agent.
[0066] The antifungal agent (preservative) is not particularly limited and can be appropriately selected depending on the desired use and purpose.Specific examples include isothiazoline preservatives such as 1,2-benzoisothiazol-3(2H)-one (BIT), 2-methyl-4-isothiazolin-3-one, and 5-chloro-2-methyl-4-isothiazolin-3-one, and phenoxyethanol.
[0067] The solubilizing agent is a substance that is present when the water-soluble polymer is dissolved in a dispersion medium (solvent) to improve the solubility of the water-soluble polymer. The first liquid and / or the second liquid according to one embodiment of the present invention may further contain a solubilizing agent.
[0068] Examples of the dissolution aid include alcohol compounds such as methanol, ethanol, 1-propanol, 2-propanol, ethylene glycol, and propylene glycol; ether compounds such as diethylene glycol diethyl ether, 2-methoxyethanol, 2-ethoxyethanol, diethylene glycol, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, triethylene glycol, triethylene glycol monomethyl ether, tetraethylene glycol, dipropylene glycol, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, tripropylene glycol monomethyl ether, diacetone alcohol, 2-methoxyethyl acetate, 2-ethoxyethyl acetate, and diethylene glycol monoethyl ether acetate; and ketone compounds such as acetone, methyl ethyl ketone, acetylacetone, and cyclohexanone. These dissolution aids can be used alone or in combination of two or more.
[0069] The first liquid and / or the second liquid according to the present invention may contain a surfactant other than the nonionic surfactant (hereinafter referred to as "other surfactant") within a range that does not impair the effects of the present invention. The other surfactant may be a surfactant having at least one functional group selected from a cationic group and an anionic group in the molecule. The number average molecular weight (Mn) of the other surfactant is preferably 100 to 1000. The other surfactant may be used alone or in combination of two or more. When the second liquid according to the present invention contains the other surfactant, the mass ratio of the nonionic surfactant to the other surfactant (nonionic surfactant:other surfactant) is preferably 80:20 to 99.99:0.01, more preferably 90:10 to 99.9:0.1.
[0070] In the present invention, the pH of the polishing composition obtained by mixing the first liquid and the second liquid is preferably from 2 to 4. The polishing composition of the present invention contains abrasive grains, a polishing suppressor, an organic acid, and an oxidizing agent as essential components, but if it is difficult to obtain the desired pH using these alone, the pH may be adjusted by adding a pH adjuster to the first liquid and / or the second liquid within a range that does not impair the effects of the present invention.
[0071] The pH adjuster may be either an alkali or an acid other than the above organic acids (i.e., an inorganic acid). However, in order to further exert the effects of the present invention, it is preferable that the polishing composition according to the present invention does not contain an inorganic acid. The pH adjuster may be used alone or in combination of two or more kinds.
[0072] Specific examples of inorganic acids used as pH adjusters include hydrochloric acid, sulfuric acid, nitric acid, hydrofluoric acid, boric acid, carbonic acid, hypophosphorous acid, phosphorous acid, and phosphoric acid.
[0073] Examples of bases that can be used as pH adjusters include, for example, hydroxides or salts of Group 1 elements, hydroxides or salts of Group 2 elements, quaternary ammonium hydroxides or salts thereof, etc. Examples of salts include carbonates, bicarbonates, sulfates, acetates, etc.
[0074] The amount of the pH adjuster added to the first liquid and / or the second liquid is not particularly limited, and may be appropriately adjusted so that the polishing composition has a desired pH.
[0075] [Polishing composition] In the polishing method according to the present invention, the first liquid and the second liquid are mixed during or immediately before polishing to obtain a polishing composition. When the first liquid and the second liquid are mixed during polishing, the first liquid and the second liquid are mixed on a platen to obtain a polishing composition. When the first liquid and the second liquid are mixed immediately before polishing, the first liquid and the second liquid are mixed in a container or a pipe to obtain a polishing composition. The polishing composition according to the present invention will be described.
[0076] [pH] The pH of the polishing composition according to the present invention is preferably 2 or more and 4 or less, more preferably 2.0 or more and 4.0 or less, even more preferably more than 2 and less than 4, particularly preferably 2.2 or more and 3.8 or less, and most preferably 2.5 or more and 3.5 or less. When the pH is within the above range, the desired effect of the present invention is more effectively exhibited.
[0077] The pH of the polishing composition can be measured specifically by the method described in the Examples.
[0078] [Zeta potential of abrasive grains] In the polishing composition according to the present invention, the abrasive grains have a positive zeta potential. The lower limit of the zeta potential of the abrasive grains in the polishing composition is preferably 5 mV or more, more preferably 10 mV or more, even more preferably 15 mV or more, particularly preferably 18 mV or more, and most preferably 20 mV or more. The upper limit of the zeta potential of the abrasive grains in the polishing composition is preferably 70 mV or less, more preferably 60 mV or less, even more preferably 50 mV or less, particularly preferably 40 mV or less, and most preferably 35 mV or less. That is, the zeta potential of the abrasive grains in the polishing composition is preferably 5 mV or more and 70 mV or less, more preferably 10 mV or more and 60 mV or less, even more preferably 15 mV or more and 50 mV or less, particularly preferably 18 mV or more and 40 mV or less, and most preferably 20 mV or more and 35 mV or less.
[0079] In the polishing composition, if the abrasive grains have the above-mentioned zeta potential, the polishing selectivity can be controlled for the polishing object containing two or more different film types. By the abrasive grains having the above-mentioned zeta potential, for example, the titanium nitride film can be polished at a higher polishing speed, and the polishing speed of the titanium nitride film becomes higher than the polishing speed of the silicon oxide film (the polishing selectivity becomes higher).
[0080] In this specification, the zeta potential of the abrasive grains is a value measured by the method described in the Examples. The zeta potential of the abrasive grains can be adjusted by the amount of cationic groups contained in the abrasive grains, the pH of the polishing composition, etc.
[0081] [Content of each ingredient] The content (concentration) of the abrasive grains in the polishing composition is preferably 0.1% by mass or more, more preferably 0.2% by mass or more, even more preferably 0.5% by mass or more, and particularly preferably more than 0.5% by mass, based on the total mass of the polishing composition. The upper limit of the content of the abrasive grains in the polishing composition is preferably 10% by mass or less, more preferably 5% by mass or less, even more preferably 4% by mass or less, and particularly preferably less than 4% by mass, based on the total mass of the polishing composition. That is, the content of the abrasive grains in the polishing composition is preferably 0.1% by mass or more and 10% by mass or less, more preferably 0.2% by mass or more and 5% by mass or less, even more preferably 0.5% by mass or more and 4% by mass or less, and particularly preferably more than 0.5% by mass and less than 4% by mass. In one embodiment, the content (concentration) of the abrasive grains in the polishing composition is 0.5% by mass or more and 5.0% by mass or less.
[0082] If the content of the abrasive grains is within this range, the polishing selectivity can be controlled for the polishing object containing two or more different film types. According to one embodiment, if the content of the abrasive grains is within this range, the titanium nitride film can be polished at a higher polishing rate, and the polishing rate of the titanium nitride film is higher than the polishing rate of the silicon oxide film (the polishing selectivity becomes higher). When the polishing composition contains two or more types of abrasive grains, the content of the abrasive grains refers to the total amount of these.
[0083] The content (concentration) of the polishing inhibitor (nonionic surfactant) in the polishing composition is not particularly limited, but is preferably 0.001 mass% or more, more preferably 0.002 mass% or more, even more preferably 0.003 mass% or more, particularly preferably 0.005 mass% or more, and most preferably 0.008 mass% or more, based on the total mass of the polishing composition. The content of the polishing inhibitor (nonionic surfactant) in the polishing composition is preferably 10 mass% or less, more preferably 5 mass% or less, even more preferably 2 mass% or less, particularly preferably 1 mass% or less, and most preferably 0.8 mass% or less, based on the total mass of the polishing composition. If the content of the polishing inhibitor (nonionic surfactant) is in such a range, the polishing selectivity can be controlled in a polishing object containing two or more different film types. According to one embodiment, when the content of the polishing inhibitor (nonionic surfactant) is within such a range, the polishing rate of the silicon oxide film can be further suppressed, and the polishing rate of the titanium nitride film becomes higher than the polishing rate of the silicon oxide film (the polishing selectivity becomes higher).
[0084] The content (concentration) of the organic acid in the polishing composition is preferably 0.001% by mass or more, more preferably 0.002% by mass or more, based on the total mass of the polishing composition. The content of the organic acid in the polishing composition is preferably 10% by mass or less, more preferably 5% by mass or less, based on the total mass of the polishing composition. If the content of the organic acid is within this range, the polishing selectivity can be controlled for an object to be polished that includes two or more different film types. According to one embodiment, if the content of the organic acid is within this range, the titanium nitride film can be polished at a higher polishing rate, and the polishing rate of the titanium nitride film is higher than the polishing rate of the silicon oxide film (the polishing selectivity is higher).
[0085] In the polishing composition according to the present invention, the organic acid plays a role as a pH adjuster for the polishing composition, and therefore the amount of the organic acid added may be appropriately adjusted so that the pH of the polishing composition is, for example, from 2 to 4. As an example, when 10-camphorsulfonic acid is used, the amount of the organic acid added is preferably from 0.005% by mass to 1% by mass, more preferably from 0.008% by mass to 0.500% by mass, and particularly preferably from 0.010% by mass to 0.100% by mass, based on the total mass of the polishing composition.
[0086] The content of the oxidizing agent in the polishing composition is suitably 0.001 mol / L (1 mM) or more. For example, from the viewpoint of improving the polishing speed of titanium nitride film, in some embodiments, the content of the oxidizing agent is preferably 0.005 mol / L (5 mM) or more, more preferably 0.008 mol / L (8 mM) or more, even more preferably 0.01 mol / L (10 mM) or more, particularly preferably 0.015 mol / L (15 mM) or more, and most preferably 0.02 mol / L (20 mM) or more, from the viewpoint of improving the polishing speed of titanium nitride film. Also, for example, from the viewpoint of improving the polishing selectivity ratio of titanium nitride / silicon oxide, the content of the oxidizing agent is suitably 10 mol / L (10,000 mM) or less, preferably 5 mol / L (5,000 mM) or less, more preferably 3 mol / L (3,000 mM) or less (e.g., 2.5 mol / L (2,500 mM) or less, or 2 mol / L (2,000 mM) or less), even more preferably 1 mol / L (1,000 mM) or less, particularly preferably 0.5 mol / L (500 mM) or less, and most preferably 0.1 mol / L or less.
[0087] From the above, the content of the oxidizing agent in the polishing composition is suitably 0.001 mol / L or more and 10 mol / L or less, preferably 0.005 mol / L or more and 5 mol / L or less, more preferably 0.008 mol / L or more and 3 mol / L or less, even more preferably 0.01 mol / L or more and 1 mol / L or less, particularly preferably 0.015 mol / L or more and 0.5 mol / L or less, and most preferably 0.02 mol / L or more and 0.1 mol / L or less.
[0088] [Polishing method] As described above, each component of the polishing composition according to the present invention has been described. The polishing composition according to the present invention may be prepared by separately preparing these components as a first liquid and a second liquid, and mixing the first liquid and the second liquid immediately before or during polishing (i.e., when the object to be polished is polished) to form the above-mentioned polishing composition. As the third liquid, only a dispersion medium may be prepared, and the first liquid, the second liquid, and the third liquid may be mixed immediately before or during polishing (i.e., when the object to be polished is polished) to form the above-mentioned polishing composition. In the present invention, "immediately before polishing" means the time up to 24 hours before the object to be polished is polished. Therefore, mixing immediately before polishing is performed 24 hours before or after the object to be polished is polished.
[0089] In the polishing method according to the present invention, the first liquid and the second liquid may be the first liquid and the second liquid, respectively, which have been prepared and / or stored in advance. That is, in the polishing method according to the present invention, the preparation of the first liquid and the second liquid is not an essential step, and the first liquid and the second liquid which have been prepared in advance may be used. When preparing the first liquid and the second liquid, the first liquid may be prepared by mixing the components of the first liquid, and the second liquid may be prepared by mixing the components of the second liquid. Thus, in one embodiment, the polishing method according to the present invention includes a step of mixing an abrasive grain and a dispersion medium to prepare the first liquid; and a step of mixing an acid, a polishing inhibitor, an oxidizing agent, and a dispersion medium to prepare the second liquid. The temperature at which the first liquid and the second liquid are mixed is not particularly limited, but is preferably 15°C or more and 45°C or less, and more preferably 20°C or more and 40°C or less. The method for mixing the first liquid and the second liquid is not particularly limited as long as the components are dissolved, and examples thereof include a method in which the mixture is stirred by a known stirring means.
[0090] The polishing method according to the present invention may store the first liquid and the second liquid prepared or prepared as described above. That is, in one embodiment, the polishing method according to the present invention may include a step of preparing or preparing the components of the polishing composition separately as a first liquid and a second liquid, and storing the first liquid and the second liquid.
[0091] The temperature at which the first liquid and the second liquid are stored is preferably 15°C or higher and 45°C or lower, more preferably 20°C or higher and 40°C or lower, even more preferably 25°C or higher and 35°C or lower, and particularly preferably 20°C or higher and 30°C or lower.
[0092] According to the polishing method of the present invention, the object to be polished is polished using a polishing composition obtained by mixing the first liquid and the second liquid prepared in advance as described above immediately before or during polishing (i.e., when the object to be polished is being polished). Thus, according to one embodiment of the polishing method of the present invention, the method includes a step of polishing the object to be polished using a polishing composition obtained by mixing the first liquid and the second liquid immediately before or during polishing (i.e., when the object to be polished is being polished).
[0093] In the polishing step, for example, a polishing composition is supplied between the object to be polished (e.g., an object to be polished containing titanium nitride and silicon oxide) in a state where the object to be polished is pressed against a polishing pad (polishing cloth) of a polishing platen, and the object to be polished and the polishing platen are moved relatively to polish the object to be polished. In the polishing step, for example, at least a part of the object to be polished is removed by polishing. The object to be polished may be, for example, a film (film to be polished).
[0094] The method of preparing a polishing composition by mixing the above-mentioned first liquid and second liquid immediately before or during polishing, that is, the method of mixing the first liquid and the second liquid, includes the following methods. For example, the following can be used: a method of sending the first liquid and the second liquid through separate pipes, and then merging and mixing the liquids to supply them onto the polishing platen; a method of mixing the first liquid and the second liquid in advance immediately before polishing and supplying them onto the polishing platen; a method of sending the first liquid and the second liquid through separate pipes, and then supplying the first liquid and the second liquid onto the polishing platen, respectively.
[0095] As described above, when the first liquid and the second liquid are mixed to obtain a polishing composition, the mixing ratio (mass ratio) of the first liquid to the second liquid is preferably 30:70 to 99:1, more preferably 40:60 to 98:2, even more preferably 50:50 to 95:5, particularly preferably 60:40 to 90:10, and most preferably 30:70 to 85:15.
[0096] The speed at which the polishing composition is supplied onto the polishing platen (the combined supply speed of the first and second liquids when the first and second liquids are mixed during polishing) is preferably such that the surface of the polishing pad is always covered with the polishing composition of the present invention, and is, for example, preferably from 10 mL / min to 1200 mL / min, more preferably from 20 mL / min to 1000 mL / min, even more preferably from 50 mL / min to 800 mL / min, particularly preferably from 70 mL / min to 700 mL / min, and most preferably from 100 mL / min to 500 mL / min.
[0097] In one embodiment, the first liquid and the second liquid are mixed immediately before polishing, preferably up to 20 hours, more preferably up to 18 hours, even more preferably up to 15 hours, particularly preferably up to 12 hours, and most preferably up to 10 hours before the object to be polished is to be polished.
[0098] The polishing apparatus used in the polishing method of the present invention can be a general polishing apparatus equipped with a holder for holding a substrate having an object to be polished, a motor capable of changing the rotation speed, and a polishing platen to which a polishing pad (polishing cloth) can be attached.
[0099] As the polishing pad, general nonwoven fabric, polyurethane, porous fluororesin, etc. can be used without any particular restrictions. The polishing pad is provided with grooves to hold the polishing liquid. It is preferable that the above is done.
[0100] Regarding the polishing conditions, for example, the rotation speed of the polishing platen and the carrier was 10 rpm (0.17 s -1 ) or more 500rpm (8.33s -1 The pressure (polishing pressure) applied to the substrate having the object to be polished is preferably 0.5 psi (3.4 kPa) or more and 10 psi (68.9 kPa).
[0101] The method for supplying the polishing composition to the polishing pad is not particularly limited, and for example, a method of continuously supplying the polishing composition with a pump or the like can be used.
[0102] After polishing, the object to be polished (e.g., a substrate) is washed with running water, and water droplets adhering to the substrate are removed using a spin dryer or the like, followed by drying to obtain a polished object to be polished (e.g., a polished substrate).
[0103] [Polished object] Examples of materials contained in the object to be polished used in the polishing method according to the present invention include silicon oxide (SiO2), silicon nitride (SiN), silicon carbonitride (SiCN), polycrystalline silicon (polysilicon), non-crystalline silicon (amorphous silicon), metals, SiGe, Group 13 elements, etc. The object to be polished according to the present invention is preferably an object to be polished that contains two or more different film types.
[0104] Examples of films containing silicon oxide include, for example, TEOS (Tetraethyl Orthosilicate) type silicon oxide films (hereinafter, simply referred to as "TEOS films") produced using tetraethyl orthosilicate as a precursor, HDP (High Density Plasma) films, USG (Undoped Silicate Glass) films, PSG (Phosphorus Silicate Glass) films, BPSG (Boron-Phospho Silicate Glass) films, and RTO (Rapid Thermal Oxidation (CO) films and the like.
[0105] Examples of the metal-containing film include tungsten (W) film, titanium nitride (TiN) film, ruthenium (Ru) film, platinum (Pt) film, gold (Au) film, hafnium (Hf) film, cobalt (Co) film, nickel (Ni) film, copper (Cu) film, aluminum (Al) film, and tantalum (Ta) film. From the viewpoint of improving electrical conductivity, W film, TiN film, Ru film, Pt film, or Au film is preferably used. In one embodiment, the polishing composition according to the present invention can be used to suitably polish a polishing target containing a metal.
[0106] The object to be polished according to the present invention may have a layer containing 40 mass% or more of a Group 13 element (hereinafter, simply referred to as a Group 13 element layer). Examples of Group 13 elements include boron (B), aluminum (Al), gallium (Ga), and indium (In). The Group 13 elements may be used alone or in combination of two or more.
[0107] The Group 13 element layer may contain elements other than the Group 13 elements. Examples of the other elements include silicon (Si), hydrogen (H), nitrogen (N), oxygen (O), carbon (C), phosphorus (P), germanium (Ge), etc. These other elements may be contained alone or in combination of two or more.
[0108] The lower limit of the amount of the Group 13 element contained in the Group 13 element layer is 40 mass% or more, preferably 45 mass% or more, and more preferably 50 mass% or more, based on the mass of the entire layer. The upper limit of the amount of the Group 13 element contained in the Group 13 element layer is preferably 100 mass% or less, more preferably 95 mass% or less, and even more preferably 90 mass% or less, based on the mass of the entire layer.
[0109] The polishing method according to the present invention can control the polishing selectivity, that is, improve the polishing rate of one film type and suppress the polishing rate of another film type in a polishing object containing two or more different film types. The polishing method according to the present invention is preferably used for polishing an object containing a silicon oxide film or a titanium nitride film. Therefore, the polishing composition produced by the polishing method according to the present invention is preferably used for polishing an object containing a silicon oxide film or a silicon nitride film.
[0110] In one embodiment, the object to be polished according to the present invention preferably contains an element of Group 13. Therefore, the polishing composition of the present invention is preferably used for polishing an object to be polished that contains an element of Group 13.
[0111] Furthermore, the shape of the object to be polished is not particularly limited. In one embodiment of the present invention, the polishing composition can be preferably applied to polishing an object to be polished having a flat surface, such as a plate-like or polyhedral shape.
[0112] [Polishing composition kit] According to the polishing method of the present invention, a polishing composition kit for use in the polishing method of the present invention is provided. The polishing composition kit includes the first liquid and the second liquid. Here, the first liquid and the second liquid are stored separately from each other. The polishing method of the present invention can be suitably carried out using the polishing composition kit having such a configuration.
[0113] Therefore, according to the present invention, there is also provided a polishing composition kit comprising a first liquid containing an abrasive grain having a positive zeta potential and a dispersing medium, and a second liquid containing an acid, a polishing inhibitor, an oxidizing agent and a dispersing medium, wherein the acid is an organic acid, the polishing inhibitor contains a nonionic surfactant, and the oxidizing agent is hydrogen peroxide.
[0114] The polishing composition kit according to the present invention is a kit used for producing a polishing composition used in the polishing method according to the present invention, and includes the first liquid. The polishing composition is preferably used as the first liquid constituting the polishing composition kit according to the present invention, for example.
[0115] The polishing composition kit according to the present invention is a kit used for producing a polishing composition used in the polishing method according to the present invention, and includes the above-mentioned second liquid. The above-mentioned polishing composition is preferably used as the second liquid constituting the polishing composition kit according to the present invention, for example.
[0116] The method for producing a polishing composition according to the present invention includes using the polishing composition kit to mix the first liquid and the second liquid immediately before or during polishing so that the pH is from 2 to 4. The method for adjusting the pH of the resulting polishing composition to 2 to 4 is not particularly limited, and may include a method of adjusting the pH of the first liquid and / or the second liquid, or a method of further adding a pH adjuster when mixing immediately before or during polishing.
[0117] [Method of manufacturing semiconductor substrate] The polishing method according to one embodiment of the present invention is preferably used for polishing an object to be polished that contains two or more different film types. The polishing method according to the present invention is preferably used for polishing an object to be polished that contains, for example, titanium nitride and silicon oxide. Thus, the present invention provides a polishing method comprising polishing an object to be polished using the polishing composition kit according to the present invention. The present invention also provides a method for producing a semiconductor substrate comprising polishing a semiconductor substrate using the polishing composition kit according to the present invention. The present invention also provides a method for producing a semiconductor substrate comprising polishing a semiconductor substrate by the polishing method according to the present invention.
[0118] [Polishing selectivity of titanium nitride / silicon oxide] The polishing method according to the present invention can polish an object to be polished that contains silicon oxide and titanium nitride at a specific polishing rate ratio. The polishing method according to the present invention can be preferably applied to polishing (e.g., finish polishing) an object to be polished that contains silicon oxide and titanium nitride.
[0119] The lower limit of the polishing speed of titanium nitride is preferably more than 500 Å / min, more preferably 520 Å / min or more, even more preferably 540 Å / min or more, particularly preferably 550 Å / min or more, and most preferably 580 Å / min or more. By the polishing speed exceeding 500 Å / min, the polishing of titanium nitride proceeds favorably. The upper limit of the polishing speed of the titanium nitride film is not particularly limited, but in practical use, it is 8000 Å / min or less. Note that 1 Å=0.1 nm.
[0120] The upper limit of the polishing speed of silicon oxide is preferably 50 Å / min or less, more preferably 40 Å / min or less, and even more preferably 30 Å / min or less. By making the polishing speed 50 Å / min or less, the polishing selectivity of titanium nitride to silicon oxide can be further improved. There is no particular limit to the lower limit of the polishing speed of the silicon oxide film, but in practical use, it is 5 Å / min or more. The polishing selectivity of titanium nitride to silicon oxide is preferably 15 or more, more preferably 20 or more, even more preferably 21 or more, and particularly preferably 22 or more.
[0121] Although the embodiments of the present invention have been described in detail, it is apparent that the same are illustrative and exemplary, not restrictive, and the scope of the present invention should be interpreted by the appended claims.
[0122] The present invention encompasses the following aspects and configurations.
[0123] [1] A polishing method for polishing an object to be polished using a polishing composition, the polishing composition comprising an abrasive, an acid, a polishing inhibitor, an oxidizing agent, and a dispersing medium, the abrasive has a positive zeta potential, the acid is an organic acid, and the polishing inhibitor comprises a nonionic surfactant, the components of the polishing composition are prepared separately as a first liquid and a second liquid, the first liquid comprises the abrasive and the dispersing medium, the second liquid comprises the acid, the polishing inhibitor, the oxidizing agent, and the dispersing medium, and the first liquid and the second liquid are mixed immediately before or during polishing of the object to be polished.
[0124] [2] The polishing method according to the above [1], wherein the abrasive grains are cation-modified silica, the polishing inhibitor is a compound having a polyalkylene glycol structure, and the organic acid is an organic acid having a sulfonic acid group.
[0125] [3] The polishing method according to the above [1] or [2], wherein the polishing inhibitor is polyethylene glycol or polypropylene glycol having a number average molecular weight of 200 or more and less than 1,000.
[0126] [4] The polishing method according to any one of the above [1] to [3], wherein the polishing composition has a pH of 2 or more and 4 or less.
[0127] [5] The polishing method according to any one of the above [1] to [4], further comprising a step of polishing an object to be polished with a polishing composition obtained by mixing the first liquid and the second liquid.
[0128] [6] A polishing composition kit comprising: a first liquid containing an abrasive having a positive zeta potential and a dispersing medium; and a second liquid containing an acid, a polishing inhibitor, an oxidizing agent, and a dispersing medium, wherein the acid is an organic acid, and the polishing inhibitor contains a nonionic surfactant.
[0129] [7] A method for producing a polishing composition, comprising mixing the first liquid and the second liquid immediately before or during polishing using the polishing composition kit described in [6] above so that the pH is 2 or more and 4 or less. EXAMPLES
[0130] The present invention will be described in more detail with reference to the following examples and comparative examples. However, the technical scope of the present invention is not limited to the following examples. In addition, unless otherwise specified, "%" and "parts" mean "% by mass" and "parts by mass", respectively.
[0131] <Average primary particle size of abrasive grains> The average primary particle size of the abrasive grains was calculated from the specific surface area of the silica particles measured by the BET method using "Flow Sorb II 2300" manufactured by Micromeritics, and the density of the abrasive grains.
[0132] <Average secondary particle size of abrasive grains> The average secondary particle diameter of the abrasive grains was measured as the volume average particle diameter (arithmetic mean diameter based on volume; Mv) using a dynamic light scattering particle size / particle size distribution analyzer UPA-UTI151 (manufactured by Nikkiso Co., Ltd.).
[0133] <Average degree of association of abrasive grains> The average degree of association of the abrasive grains was calculated by dividing the value of the average secondary particle size of the abrasive grains by the value of the average primary particle size of the abrasive grains.
[0134] <Zeta potential of abrasive grains> The zeta potential of the abrasive grains in the polishing composition was measured by subjecting the polishing composition to a Zetasizer Nano manufactured by Malvern Panalytical and measuring it using the laser Doppler method (electrophoretic light scattering measurement method) at a measurement temperature of 25°C, and calculating the zeta potential by analyzing the obtained data using the Smoluchowski formula.
[0135] <pH of polishing composition> The pH of the polishing composition was measured using a glass electrode type hydrogen ion concentration indicator (Model number: F-23, manufactured by Horiba, Ltd.) and three-point calibration was performed using standard buffer solutions (phthalate pH buffer solution, pH: 4.01 (25°C), neutral phosphate pH buffer solution, pH: 6.86 (25°C), carbonate pH buffer solution, pH: 10.01 (25°C)).The glass electrode was then placed in the polishing composition and the pH value was recorded after stabilization for at least 2 minutes.
[0136] [Preparation of the first and second liquids] As described below, mixed liquid A was prepared as the first liquid, and mixed liquid B was prepared as the second liquid. Hereinafter, the polishing composition obtained by mixing the first liquid and the second liquid is referred to as mixed liquid C (i.e., a mixture of mixed liquid A and mixed liquid B).
[0137] (Preparation of Mixture A) In the same manner as in Example 1 of JP 2005-162533 A, γ-aminopropyltriethoxysilane (APTES) was used as a silane coupling agent at a concentration of 3.5 mmol (3.1 mM) per 1 L of an aqueous dispersion of silica sol (silica concentration=20% by mass), to prepare a cocoon-shaped cation-modified colloidal silica having an average primary particle size of 25.0 nm, an average secondary particle size of 50.0 nm, an average degree of association of 2.0, and an aspect ratio of 1.2.
[0138] The cation-modified colloidal silica obtained above was added as an abrasive grain to pure water as a dispersion medium at room temperature (25°C) so as to have a concentration of 1.1% by mass. Furthermore, 2-methyl-4-isothiazolin-3-one (manufactured by The Dow Chemical Company) as an antifungal agent and 0.03% by mass of (+)-10-camphorsulfonic acid as an acid were added to have a concentration of 0.018 mM, and the mixture was stirred and mixed for 30 minutes at room temperature (25°C) to obtain a mixed solution A. The pH of the obtained mixed solution A was measured and found to be 3.3.
[0139] (Preparation of Mixture B) Polypropylene glycol (PPG) (Mw: 400, manufactured by Sanyo Chemical Industries, Ltd.) was added in an amount of 0.05 mass%, (+)-10-camphorsulfonic acid as an acid was 0.07 mass%, 2-methyl-4-isothiazolin-3-one (manufactured by The Dow Chemical Company, Ltd.) as an antifungal agent was 0.04 mM, and 31 mass% aqueous hydrogen peroxide solution (manufactured by Santoku Chemical Industry Co., Ltd.) as an oxidizing agent was added in an amount of 135 mM, and the mixture was stirred and mixed at room temperature (25°C) for 30 minutes to obtain a mixed solution B. The pH of the obtained mixed solution B was measured and found to be 2.5.
[0140] The obtained mixed solution A and mixed solution B were mixed in a volume ratio of 4:1 to obtain a polishing composition (mixed solution C). The zeta potential of the cation-modified colloidal silica in the polishing composition (mixed solution C) was measured according to the above method, and was 27 mV. Furthermore, the particle size of the cation-modified colloidal silica in the polishing composition (mixed solution C) obtained in the same manner was the same as the particle size of the cation-modified colloidal silica used. Moreover, the pH of the polishing composition (mixed solution C) obtained in the same manner was 3.0.
[0141] [Preparation of polishing composition (mixed liquid C)] In Examples 1 to 5 and Comparative Examples 1 to 3, the step of mixing mixed liquid A and mixed liquid B to prepare a polishing composition (mixed liquid C) was performed in three ways: during polishing, immediately before polishing, and beforehand. Unless otherwise specified, "storage" includes not only the period (time) during which mixed liquid A and mixed liquid B are separate, but also the period (time) during which mixed liquid A and mixed liquid B are mixed to form mixed liquid C, while "standby" means the period (time) during which mixed liquid A and mixed liquid B are mixed to form mixed liquid C.
[0142] (Examples 1 to 5) In Examples 1 to 3, mixed liquid A and mixed liquid B were stored under the storage conditions shown in Table 1, and then mixed liquid A and mixed liquid B were supplied onto the platen according to the "supply method by mixing during polishing" described below. In Examples 4 and 5, mixed liquid A and mixed liquid B were stored under the storage conditions shown in Table 1, and then mixed liquid A and mixed liquid B were mixed according to the "supply method by mixing immediately before polishing" to supply mixed liquid C onto the platen. Note that in Examples 4 and 5, storage corresponds to "standby".
[0143] (Comparative Examples 1 to 3) In Comparative Examples 1 to 3, mixed liquid A and mixed liquid B were prepared, and then mixed liquid A and mixed liquid B were mixed to obtain mixed liquid C. Then, mixed liquid C was stored (on standby) under the storage conditions shown in Table 1, and then mixed liquid C was supplied onto the platen according to the "supply method by pre-mixing". Note that in Comparative Examples 1 to 3, storage corresponds to "on standby".
[0144] [Supply method by mixing during polishing] The ends of two pipes were placed on the surface plate, and one end of each pipe was placed in mixed liquid A and the other end of each pipe was placed in mixed liquid B so that mixed liquid A was supplied from one pipe onto the surface plate, and mixed liquid B was supplied from the other pipe onto the surface plate. Each of mixed liquids A and B was adjusted by a pump or the like to be sent onto the surface plate at a predetermined speed.
[0145] Mixture A was fed onto the surface plate at a rate of 200 mL / min and mixture B was fed at a rate of 50 mL / min. The nozzle was adjusted so that a single liquid was applied onto the surface plate, and polishing was performed under the following conditions.
[0146] [Pre-mix supply method] Mixture A and mixture B were mixed in a ratio of 4:1 just before polishing to obtain mixture C, which was then stored (standby) under the storage conditions listed in Table 1. After a predetermined time of storage (standby), mixture C was sent onto a platen at a speed of 250 mL / min, and polished under the following conditions. The time before polishing (standby time from preparation of mixture C until polishing) referred to as just before polishing was within 24 hours. The standby time from preparation of mixture C until polishing is the storage time listed in Table 1. That is, in the case of immediately before mixing, storage corresponds to "standby". In Example 4, polishing was started within 10 minutes after preparation of mixture C, so the storage (standby) time was set to 0.
[0147] [Pre-mix supply method] Mixture A and mixture B were mixed in advance in a ratio of 4:1 to obtain mixture C, which was then stored (standby) under the storage conditions listed in Table 1. After a prescribed period of storage (standby), mixture C was sent onto the platen at a rate of 250 mL / min and polished under the following conditions. The waiting time from preparation of mixture C to polishing, referred to as "in advance," is the storage time listed in Table 1. That is, in the case of pre-mixing, storage corresponds to "standby."
[0148] <Storage conditions> Mixture A, Mixture B, and Mixture C, which was a mixture of Mixture A and Mixture B in a ratio of 4:1, were placed in polypropylene containers and stored at 25°C and 80°C for 0 to 96 hours. Using each mixed solution after storage, polishing was performed using the mixed solution addition method shown in the above [Method of supplying by mixing during polishing], [Method of supplying by mixing immediately before polishing], and [Method of supplying by mixing in advance], and polishing performance evaluation was performed. By comparing the polishing speeds of each of the products stored for 0 to 96 hours at 25°C and 80°C, the polishing performance based on the stability of the polishing composition was evaluated.
[0149] <Evaluation of Polishing Rate of Polishing Composition> Using each of the polishing compositions prepared above, the surface of the object to be polished was polished under the following conditions: The objects to be polished were a silicon wafer (300 mm, blanket wafer) with a titanium nitride (TiN) film of 2500 Å thickness formed on its surface, and a silicon wafer (300 mm, blanket wafer) with a TEOS type silicon oxide (SiO2) film (hereinafter, "TEOS film") of 10000 Å thickness formed on its surface.
[0150] (Polishing equipment and polishing conditions) Polishing equipment: Ebara Corporation polishing machine (model FREX 300E) Polishing pad: Nitta DuPont Polyurethane Pad IC1000 Polishing pressure: 3.0 psi (1 psi = 6894.76 Pa) Polishing platen rotation speed: 113 rpm Supply of polishing composition: free-flowing Polishing composition supply amount: 250ml / min Polishing time: 1 minute.
[0151] (Evaluation of polishing speed) For titanium nitride films, the thickness before and after polishing was measured using a sheet resistance meter (VR120 / 08SD: manufactured by Kokusai Electric Semiconductor Services Co., Ltd.) based on the DC four-probe method. For TEOS films, the thickness before and after polishing was measured using an optical film thickness meter (ASET-f5x: manufactured by KLA-Tencor Corporation). From the measured thickness, the polishing speed for each object to be polished was calculated by dividing [(thickness before polishing) - (thickness after polishing)] by the polishing time. For titanium nitride films, if the polishing speed exceeds 500 Å / min, it is practical. For TEOS films, if it is 50 Å / min or less, it is practical.
[0152] The above evaluation results are also shown in Table 1. In Table 1, the titanium nitride film is indicated as "TiN" and the TEOS film is indicated as "SiO2".
[0153] [Table 1]
[0154] As is clear from Table 1 above, in Examples 1 to 5, while polishing titanium nitride (TiN) film at a high polishing rate, the polishing rate of silicon oxide (SiO2) film was suppressed, and a high polishing selectivity was shown. On the other hand, in Comparative Examples 1 to 3, a tendency was observed in which the polishing rate of silicon oxide film increased. This shows that differences in polishing performance occur in relation to the stability of the polishing composition. That is, it is found that the method of storing mixed liquid A (first liquid) and mixed liquid B (second liquid) separately and mixing mixed liquid A (first liquid) and mixed liquid B (second liquid) at the time of polishing or immediately before polishing to prepare mixed liquid C (polishing composition) has a high polishing selectivity of titanium nitride / silicon oxide.
[0155] Therefore, it is understood that the polishing method according to the present invention can polish a titanium nitride film at a higher polishing rate than the polishing rate for a silicon oxide film.
Claims
1. A polishing method for polishing an object to be polished using a polishing composition, comprising: The polishing composition contains an abrasive grain, an acid, a polishing inhibitor, an oxidizing agent, and a dispersion medium; The abrasive grains have a positive zeta potential; the acid is an organic acid, The polishing inhibitor contains a nonionic surfactant, The components of the polishing composition are prepared separately as a first liquid and a second liquid, the first liquid contains the abrasive grains and the dispersion medium; the second liquid contains the acid, the polishing inhibitor, the oxidizing agent, and the dispersion medium; A polishing method, wherein the first liquid and the second liquid are mixed immediately before or during polishing of the object to be polished.
2. the abrasive grains are cationically modified silica; The polishing inhibitor is a compound having a polyalkylene glycol structure, The polishing method according to claim 1 , wherein the organic acid is an organic acid having a sulfonic acid group.
3. 3. The polishing method according to claim 1, wherein the polishing inhibitor is polyethylene glycol or polypropylene glycol having a number average molecular weight of 200 or more and less than 1,000.
4. The polishing method according to claim 1 or 2, wherein the polishing composition has a pH of 2 or more and 4 or less.
5. 3. The polishing method according to claim 1, further comprising a step of polishing an object to be polished with a polishing composition obtained by mixing the first liquid and the second liquid.
6. a first liquid including an abrasive having a positive zeta potential and a dispersion medium; a second liquid containing an acid, a polishing inhibitor, an oxidizing agent, and a dispersion medium; Including, the acid is an organic acid, The polishing composition kit, wherein the polishing inhibitor contains a nonionic surfactant.
7. A method for producing a polishing composition, comprising mixing the first liquid and the second liquid immediately before or during polishing using the polishing composition kit described in claim 6 so that the pH is 2 or more and 4 or less.
Citation Information
Patent Citations
Chemical / Mechanical polishing slurry useful for copper substrate
JP1999021546A